Antisipasi Xenophobia di Era Disrupsi: Studi Kasus Keramahan Terhadap yang Berbeda Agama di Kalangan Mahasantri Milenial - Fazlul Rahman; , Faiqotul Mala (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2023)
The phenomenon of fear of being different (xenophobia), which has recently emerged in the global world, has made the issue of hospitality an urgent one to be seriously reviewed. Following Mona Siddique's argument (2015) that the problem of friendliness towards people of other religions actually boils down to a tug-of-war between two factors that attract each other within a person, namely moral factors and legal factors, This paper mainly focuses on discussing how the contestation between these two factors occurs within a student and how it affects their response to issues of hospitality towards others, to anticipate xenophobia among young Muslims in the future. This paper concludes that there is a hierarchy of value systems (represented by moral and legal values) within the students that influence their responses to issues between religious communities in general and hospitality to religious communities in particular. At this point, the potential for santri and Islamic scholarship among mahasantri significantly increases this value system and, in the end, produces very positive implications for their good understanding of hospitality towards non-Muslims